Digital Competence Model for students in Distance Education: review and update of a Brazilian proposal: revisão e atualização de uma proposta brasileira - Araújo da Silva, Ketia Kellen; Behar, Patricia Alejandra (Journal of Learning Styles, 2023)
This article deals with the study to review and update the Digital Competence Model (CD) for students in Distance Education (DE) (MCompDigEaD). Since 2018, the model has been used in teacher training and building the digital competences of students in this modality in Brazil. However, the rapid digitization of various aspects of society sets new requirements, and changes in the model, arising the need for a review and update. The research with a qualitative approach was carried out based on a case study with Brazilian DE teachers. Based on the analysis and cross-referencing of data, a review of vocabularies was carried out, insertion of new terms as well as the reorganization of areas, competences, and levels of proficiency. In addition to the definition of pedagogical strategies and a proposal for a self-assessment questionnaire. The expectation is that the new version can serve as a reference in identifying digital competences for students, supporting pedagogical proposals for construction and evaluation in the context of DE. Thus, the new version of MCompDigEaD 2.0 brings the digital competences framework, updated, including pedagogical strategies and the proposed self-assessment of digital competences.
Keywords: Digital competences; Distance Education; Students; Brazil